Optimal scheduling of pumped storage hydropower plants with multi-type of units in day-ahead electricity market considering water head effects - Cao, Minjian; Hu, Zechun; Cai, Jilin (Frontiers in Energy Research, 2023)
Pumped-storage hydropower plant (PSHP) is a type of valuable energy storage system and a flexible resource to the modern power system with increasing renewable energy integration. As independent market participants, a PSHP can participate in both the energy market and frequency regulation market to maximize its revenue and contribution to the secure and economic operation of the power system. In some PSHPs, both fixed-speed and variable-speed units are installed to improve flexibility, especially when operating in the pumping mode. However, it's difficult to deal with the nonlinear relationships among power, flow, and water head in pumping and generating modes. This paper proposes iterative solution methods for scheduling the PSHP by considering the relationship between power and flow at different water heads for different types of units. The scheduling problem is established as a scenario-based optimization formulation by considering PSHP's participation in both the energy market and frequency regulation market. In each iteration, the optimal dispatch model is formulated as a Mixed Integer Linear Programming (MILP) problem. Case studies are performed and simulation results validate the effectiveness of the model and the iterative solution methods.